2021
DOI: 10.1007/s10287-021-00418-4
|View full text |Cite
|
Sign up to set email alerts
|

The spot and balancing markets for electricity: open- and closed-loop equilibrium models

Abstract: The increasing penetration of inflexible and fluctuating renewable energy generation is often accompanied by a sequential market setup, including a day-ahead spot market that balances forecasted supply and demand with an hourly time resolution and a balancing market in which flexible generation handles unexpected imbalances closer to real-time and with a higher time resolution. Market characteristics such as time resolution, the time of market offering and the information available at this time, price elastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous studies have characterised learned collusive behaviour in different types of markets [35,36], showing that participants with excess capacity can achieve collusive equilibria. One study [37] has examined asymmetries in capacity and reported the degree of asymmetry that makes collusion difficult to sustain.…”
Section: Collusion Of Supply-side and Demand-side Electricity Marketsmentioning
confidence: 99%
“…Previous studies have characterised learned collusive behaviour in different types of markets [35,36], showing that participants with excess capacity can achieve collusive equilibria. One study [37] has examined asymmetries in capacity and reported the degree of asymmetry that makes collusion difficult to sustain.…”
Section: Collusion Of Supply-side and Demand-side Electricity Marketsmentioning
confidence: 99%